Health economic evaluations comparing faecal microbiota transplantation with antibiotics for treatment of recurrent Clostridioides difficile infection: A systematic review - Lianna Hede Hammeken; Simon Mark Dahl Baunwall; Christian Lodberg Hvas; Lars Holger Ehlers (Health Economics Review, 2021)
Background: Faecal microbiota transplantation (FMT) is increasingly being used in the treatment of recurrent Clostridioides difficile infection (rCDI). Health economic evaluations may support decision-making regarding the implementation of FMT in clinical practice. Previous reviews have highlighted several methodological concerns in published health economic evaluations examining FMT. However, the impact of these concerns on the conclusions of the studies remains unclear. Aims: To present an overview and assess the methodological quality of health economic evaluations that compare FMT with antibiotics for treatment of rCDI. Furthermore, we aimed to evaluate the degree to which any methodological concerns would affect conclusions about the cost-effectiveness of FMT. Methods: We conducted a systematic literature review based on a search in seven medical databases up to 16 July 2020. We included research articles reporting on full health economic evaluations comparing FMT with antibiotic treatment for rCDI. General study characteristics and input estimates for costs, effectiveness and utilities were extracted from the articles. The quality of the studies was assessed by two authors using the Drummonds ten-point checklist. Results: We identified seven cost-utility analyses. All studies applied decision-analytic modelling and compared various FMT delivery methods with vancomycin, fidaxomicin, metronidazole or a combination of vancomycin and bezlotoxumab. The time horizons used in the analyses varied from 78 days to lifelong, and the perspectives differed between a societal, a healthcare system or a third-party payer perspective. The applied willingness-to-pay threshold ranged from 20,000 to 68,000 Great Britain pound sterling (GBP) per quality-adjusted life-year (QALY). FMT was considered the most cost-effective alternative in all studies. In five of the health economic evaluations, FMT was both more effective and cost saving than antibiotic treatment alternatives. The quality of the articles varied, and we identified several methodological concerns. Conclusions: Economic evaluations consistently reported that FMT is a cost-effective and potentially cost-saving treatment for rCDI. Based on a comparison with recent evidence within the area, the multiple methodological concerns seem not to change this conclusion. Therefore, implementing FMT for rCDI in clinical practice should be strongly considered.
Keywords: 330; Systematic review; Economic evaluation; Fecal microbiota transplantation; Faecal microbiota transplantation; Anti-bacterial agents; Decision making; Clinical decision-making